Análise dos procedimentos de ensino utilizados no curso de odontologia da Universidade Federal do Espírito Santo - Toledo, Natasha de Almeida Dutra (2017)
The teaching-learning process has undergone many changes over the years, one of the reasons is to adapt to the generation of students from schools and universities. This adaptation has also been occurring in the curriculum of higher education courses, among them Dentistry. One way of recording such changes is the analysis of the pedagogical design of the courses (PPC) of Dentistry. In the PPC there is vital and important information about the purpose of the course, courses taken (compulsory and optional), as well as the methodologies that the teachers are using to teach. The objective was to verify the teaching procedures registered in the PPC of the Dentistry course of the Federal University of Espírito Santo (UFES) and compare it with the methodology cited by the professors of the professional cycle through a questionnaire. A documentary, exploratory, descriptive and quantitative study was carried out. In the documentary research, 50% of the subjects of the vocational cycle (5th to 10th period) registered in the PPC of the UFES Dentistry course were included, forming a total of 15 subjects. In addition, the professors of the vocational cycle of the UFES Dentistry course (5th to 10th period) were interviewed from three departments: Dental Clinic, Dental Prosthesis and Social Medicine that were randomly selected. In the first stage of the interview, three questions were asked related to the discipline, period and the teaching procedures used to teach; if the teachers remembered what procedures were mentioned in the PPC and if they could be mentioned. After this step, it was carried out the reading of the Topic Methodology registered in the PPC with the teacher. After this reading, the second part of the questionnaire was applied with questions related to the topic Methodology. The teaching procedure most frequently cited by teachers was the lecture, a traditional methodology. 93% of teachers and 83% of PPC subjects reported using it. The second procedure most cited by the teachers was the seminar reported by 40% of the teachers, in the PPC he was the most cited and was present in 91% of the subjects of the PPC. Six other teaching procedures were cited, such as bibliographic research, problem-based learning (PBL), directed study, study group, discussion and problem-solving. It was observed in this research that there is little diversity in the teaching procedures cited by the teachers interviewed and described in the PPC of Dentistry of UFES. It can be concluded that there is some pedagogical difficulty or deficiency on the part of teachers to adopt new teaching procedures, including interactive teaching procedures.